no-bridge and linotte act jointly at the interhemispheric junction to build up the adult central brain of Drosophila melanogaster. - Hitier, R.; Simon, A.F.; Savarit, F.; Preat, T. (Mechanisms of Development, 2000)
The Drosophila transmembrane protein Linotte (Lio) is expressed in a glial transcient interhemispheric fibrous ring (TIFR), which was hypothesised to serve as scaffold for adult brain formation during metamorphosis. We isolated TIFR specific enhancers from the lio locus and showed that only four interhemispheric cells give rise to this complex fibrous structure. We showed that lio controls the TIFR differentiation, and confirmed the major role played by this structure in central brain metamorphosis since its destruction by apoptosis led to a pronounced adult phenotype, which included defects of lio and no-bridge (nob) mutants. lio interhemispheric expression was specifically affected in a nob(1) context, confirming that nob plays a key role in adult brain development via the TIFR.